Early childhood development and poverty reduction in the people Republic of China. - Ha, Wei; Xiao, Ye; Miyamoto, Hiroaki; Pratap, Mayank; Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
Research has shown that investing in early childhood development generates the highest rates of return and leads to better education, health, social, and economic outcomes. After decades of neglect, the Government of the Peoples Republic of China has been increasing investment in preschool education targeting children in ages 3 to 6 years since 2010. This is aligned with its recent national 14th Five Year Plan (2021 to 2025) that highlights improving the quality of human capital as an essential goal.
Keywords: Child health services -- Utilization -- China; Education -- Economic aspects; Electronic book